Pesantren dan Perguruan Tinggi - Safradji Safradji (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2019)
Pesantren as an Islamic educational institution with a boarding system is anaducation that with has astrategic position in tradinal society, especially amongstudents. This position anables pesantren to become a vehicle for effectiveempowerment for the community while remaining grounded in the cultural valuesthat underlie it.Islamic boarding schools appear to be an institution that has various facilities tobuild the potential of students, not necessarily terms of moral, intellectual andspiritual values, but also physical and material attributs.The article talk camly about the pesantren and Islamic higher educations. ThatIslamic boarding schools and Islamic higher education can be synchronize as aninnovative effort to prepare the human resources needed in this day.Keywords : Pesantren and Islamic higher EducationPendahuluan